Can Agriculture Rise to the Global Challenges? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Live from Agriculture and Rural Development Day at Rio+20, 18 June 2012 http://www.agricultureday.org Speaker: Izabella Vieira Teixeira, Minister of Environment, Brazil Join the discussion: #rio4ag http://www.twitter.com/agricultureday http://www.facebook.com/agricultureday